From Employment Pressure to Entrepreneurial Motivation: An Empirical Analysis of College Students in 14 Universities in China - Yin, Liping (Frontiers in Psychology, 2022)
Entrepreneurship is vital in solving the challenges involved in the employment of college students in China. The two viewpoints on the relationship between employment and entrepreneurship are the refugee effect and the entrepreneurial effect. However, the micro-mechanism of this association is yet to be comprehensively discussed. Based on the refugee effect and entrepreneurial effect, along with the entrepreneurial values as the mediating mechanism and the entrepreneurial environment as the moderating variable, this study establishes a theoretical model exploring the impact of employment pressure on necessity entrepreneurship and opportunity entrepreneurship of college students. Moreover, it selected 14 universities covering the eastern, central, and western regions of China. A total of 1,187 college students were surveyed anonymously using a standardized questionnaire. Then, SPSS 24.0 and Mplus 7.0 were employed to process and analyze the data, and the Structural Equation Modelling was established to test the hypothesis. The results demonstrated that employment pressure had a significant positive impact on college students’ necessity entrepreneurship. Also, employment pressure indirectly affected necessity entrepreneurship and opportunity entrepreneurship through the mediating effect of entrepreneurial values. The entrepreneurial environment (a) positively moderated the relationship between employment pressure and necessity entrepreneurship and opportunity entrepreneurship and (b) moderated the mediating effect of entrepreneurial values. That is, in a favorable entrepreneurial environment, entrepreneurial values have a stronger mediating effect. Starting from cognitive psychology, this paper explored the micro-psychological mechanism of individual employment pressure that has influenced entrepreneurial motivation. It has enriched the existing literature on the entrepreneurship theory of college students, underlining that the hypothesis on refugee effect and entrepreneurial effect is also applicable at the micro-level. On top of that, it has provided a practical reference for the employment and entrepreneurship of current Chinese college students.